2020
DOI: 10.1038/s41598-020-74492-0
|View full text |Cite
|
Sign up to set email alerts
|

Statin use is associated with lower disease severity in COVID-19 infection

Abstract: We aim to study the association of hyperlipidemia and statin use with COVID-19 severity. We analysed a retrospective cohort of 717 patients admitted to a tertiary centre in Singapore for COVID-19 infection. Clinical outcomes of interest were oxygen saturation ≤ 94% requiring supplemental oxygen, intensive-care unit (ICU) admission, invasive mechanical-ventilation and death. Patients on long term dyslipidaemia medications (statins, fibrates or ezetimibe) were considered to have dyslipidaemia. Logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
83
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 55 publications
11
83
1
3
Order By: Relevance
“…Our study found an unexpected association between reporting symptoms in keeping with COVID-19 in the previous 6 months and the use of statins, which have previously been associated with a reduced severity of COVID-19 (25). It's possible that our sample method selected out those who suffered severe COVID -19, and that statins should rather be considered marker of comorbidity (and therefore higher risk for symptomatic COVID-19) in this population.…”
Section: Discussionmentioning
confidence: 59%
“…Our study found an unexpected association between reporting symptoms in keeping with COVID-19 in the previous 6 months and the use of statins, which have previously been associated with a reduced severity of COVID-19 (25). It's possible that our sample method selected out those who suffered severe COVID -19, and that statins should rather be considered marker of comorbidity (and therefore higher risk for symptomatic COVID-19) in this population.…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, a recent investigation showed that statin use decreased the in-hospital mortality in COVID-19 patients with diabetes [ 41 ]. It has also been reported that for patients using statin during hospitalization the risk of ICU admission is reduced when compared to non-statin users [ 42 ], and that statin use decreased the risk of invasive mechanical ventilation in COVID-19 patients [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have raised the idea that statins can be used as early therapy to mitigate COVID-19-associated ARDS and cytokine storm syndrome [34][35][36] . Several recent reports showed that inhospital use of statins is associated with a reduced risk of mortality among individuals with COVID-19 [37][38][39] . There were more than 20 statins available in clinical use.…”
Section: Discussionmentioning
confidence: 99%